The Effectiveness of Acceptance and Commitment Therapy on Depression, Anxiety, and Stress in Patients with Chronic Pain in Ahvaz - Yadavari 1, Mandana; Naderi 2*, Farah; Makvandi 3, Behnam (Shahroud Journal of Medical Sciences, 2021)
Background: Chronic pain causes various problems and agonies including emotional disorders as well as limited personal, social, and occupational functioning. The present study aimed to investigate the effectiveness of acceptance and commitment therapy (ACT) on depression, anxiety, and stress in patients with chronic pain. Methods: The research method was experimental with a pre-test, post-test, and follow-up design and a control group. The study population comprised all patients with chronic pain who were referred to the medical centers of Ahvaz in 2018. Using convenience sampling, we selected 30 patients willing to participate in the study and randomly divided them into experimental (n=15) and control (n=15) groups. Both were groups tested at the beginning and end of the intervention program with the Depression, Anxiety, and Stress Scale (DASS-21). The experimental group underwent nine sessions (90-minute sessions per week) of acceptance and commitment therapy. The follow-up was performed after 60 days. Data analysis was done using SPSS version 23. Results: The mean ± SD of the post-test scores of depression, anxiety, and stress was (12.03±2.82), (10.50±2.34), and (12.50±1.72) in the experimental group and (21.33±1.84), (19.20±4.12), and (26.71±1.18) in the control group, which had significant differences with each other. The results showed that acceptance and commitment therapy effectively decreased depression, anxiety, and stress in patients with chronic pain in the experimental group (Pvalue<0.05). Conclusions: Acceptance and commitment therapy can be used as an effective intervention program to reduce depression, anxiety, and stress in patients with chronic pain. Keywords: Acceptance and commitment therapy (ACT), Depression, Anxiety, Stress, Chronic pain.